2018
DOI: 10.1002/ajoc.201800058
|View full text |Cite
|
Sign up to set email alerts
|

The Chemistry between Hypervalent Iodine(III) Reagents and Organophosphorus Compounds

Abstract: The intersection between the chemistries of hypervalent iodine (HVI) reagents and organophosphorus compounds holds significant potential. To date, the merging of these research spheres has led to novel iodane motifs, many of which have been used in new oxyphosphorylation methodologies. In addition, HVI reagents have proven easily capable of transferring electrophilic carbon-based (alkyl, aryl, al-kynyl, etc.) ligands to various phosphorus nucleophiles. Furthermore, the ease with which HVI reagents oxidize pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 99 publications
(89 reference statements)
0
6
0
Order By: Relevance
“…Hypervalent iodine compounds (HVI) are important alternatives to transition metal reagents because of their reactivity, synthetic utility, low cost, abundance, and non-toxic nature [1][2][3][4][5][6]. HVIs are involved in a multitude of reactions such as: reductive elimination, ligand exchange, oxidative addition, and ligand coupling [7,8]. The three-center four-electron bonds (3c-4e) in HVI are weak and polarizable, which is valuable in synthetic organic chemistry, as they can exchange leaving groups or accept electrophilic/nucleophilic ligands depending on their surroundings [9].…”
Section: Introductionmentioning
confidence: 99%
“…Hypervalent iodine compounds (HVI) are important alternatives to transition metal reagents because of their reactivity, synthetic utility, low cost, abundance, and non-toxic nature [1][2][3][4][5][6]. HVIs are involved in a multitude of reactions such as: reductive elimination, ligand exchange, oxidative addition, and ligand coupling [7,8]. The three-center four-electron bonds (3c-4e) in HVI are weak and polarizable, which is valuable in synthetic organic chemistry, as they can exchange leaving groups or accept electrophilic/nucleophilic ligands depending on their surroundings [9].…”
Section: Introductionmentioning
confidence: 99%
“…Hypervalent iodine­(III) compounds have attracted much attention as oxidants in organic synthesis, as they can be a replacement for transition metals with the advantage of having environmentally benign properties. Although iodine­(III) reagents are competent to conduct many organic transformations, addition of a Lewis acid such as BF 3 is often a prerequisite for a process to occur. For example, it has been shown that an iodine­(III) reagent in conjunction with BF 3 ·Et 2 O considerably accelerates the processes that yield λ 3 -diaryliodanes, olefin diacetoxylation, and a plethora of other products. In this context, Ochiai et al reported that alcohols can be selectively oxidized by hypervalent iodine­(III) compound 2 to aldehydes or ketones in the presence of BF 3 ·Et 2 O as the catalyst (Scheme ).…”
Section: Introductionmentioning
confidence: 99%
“…Table 3 Anodic oxidation for the synthesis of diaryliodonium salts Moreover, to demonstrate the efficacy of this electrochemical process for the anodic oxidation synthesis of diverse hypervalent iodine(III) reagents, we showed that simple iodobenzene can be efficiently transferred into phenyliodine diacetate (PIDA) under mild electrochemical conditions (Scheme 2). Further treatment with some common reagents led to the facile ligand exchange, derivatizing a variety of useful hypervalent iodine(III) reagents in good to excellent yields with high selectivity, including [hydroxy-(phosphoryloxy)iodo] benzene 5, [14] Koser's reagent (6), [15] amidoiodane 7, [16] iodonium imide 8, [17] alkynyliodonium salt (9), [18] aryliodonium ylide 10, [19] and Weiss' reagent 11, [20] which all find numerous applications in various bond-forming reactions. Furthermore, a range of important benziodoxole reagents containing useful OMe 12, OAc 13, CN 14, and acetylene (15) groups could be obtained in good to high yields via the ligand exchange from crude hydroxy benziodoxolone 2p (Scheme 3).…”
Section: Resultsmentioning
confidence: 99%